THE INFLUENCE OF INCOME RATIO ON INDEPENDENCE RATIO DURING COVID-19 AT LANGSA GENERAL HOSPITAL BLU - Maimun, Maimun; Khaddafi , Muammar; Naz’aina, Naz’aina (RADJA PUBLIKA, 2022)
The Regional Public Service Agency (BLUD) is a regional work unit and has a legal status that is not separate from the regional government. BLUD is formed to provide services to the community in the form of providing goods and services that are sold without prioritizing seeking profit.The population to be studied in this study is the Total Revenue of BLUDs until 2021 (during the COVID-19 pandemic). Annual BLUD income which describes its ability to cover operational expenditures for one year so that the hospital's financial independence can be seen clearly. The sample of this study uses data from the Langsa Hospital BLUD Revenue report for the period January 2019 to June 2021.GPM has a positive and significant effect on financial independence. The positive coefficient means that if the GPM increases, financial independence during the Covid-19 BLU of the Langsa Regional General Hospital will also increase. NPM has a positive and insignificant effect on financial independence. A negative coefficient means that if the NPM increases, financial independence during the Covid-19 BLU of the Langsa Regional General Hospital will decrease, and vice versa. ROI has a positive and significant effect on financial independence, a positive coefficient means that if the ROI increases, financial independence during the Covid-19 BLU of the Langsa Regional General Hospital will also increase. ROE has a negative and insignificant effect on financial independence, a negative coefficient means that if ROE increases, financial independence during Covid-19 BLU Langsa Regional General Hospital will decrease.